Synthesis, Characterization and Antimicrobial Evaluation with DFT Study of New Two-Amino-4-(4-Chlorophenyl) Thiazole Derivatives - A Mahmood Kubba, Ammar; A. A. Rahim, Nedaa (Iraqi Journal of Pharmaceutical Sciences, 2018)
2-amino-4-(4-chloro phenyl)-1,3-thiazole (1) was synthesized by refluxing thiourea with para-chloro phenacyl bromide in absolute methanol. The condensation of amine compound (1) with phenylisothiocyanate in the presence of pyridine will produce 1-(4-(4-chlorophenyl)thiazol-2-yl)-3-phenylthiourea(2), which is upon treatment with 2,4 dinitrophenyl hydrazine by conventional method, afforded 1- ( 4 - ( 4 – chlorophenyl ) thiazol – 2 – yl ) – 3 - phenylhydrazonamide,N' - ( 2 , 4 -dinitrophenyl) ,(3).The characterization of the titled compounds were performed utilizing FTIR spectroscopy, 1HNMR and CHNS elemental analysis, and by measurements of their physical properties. The synthesized compounds had been screened for their, in vitro preliminary antimicrobial activity against three Gram-positive bacteria: (Staph. aureus, Micrococcus luteus and Bacillus subtilis) and three Gram-negative bacteria : (Pseud.aeruginosa, E.coli and Proteus mirabilis) ,and two fungal strains(Candida albicans and Candida glabrata ), using a minimum inhibitory concentration (MIC) of 100 µg\ml of test compound, by well diffusion method. The derivatives showed moderate antibacterial activity against Gram-positive Staphylococcus aureus and Bacillus subtilis & high antifungal activity against Candida glabrata and Candida albicans. Computational study was performed to calculate some of thermodynamic parameters by using density functional theory (DFT)